Tuning the Photoluminescence of Graphene Quantum Dots by Fluorination. (7th November 2017) - Luo, Yi; Xu, Yongjie; Li, Ming; Sun, Lang; Hu, Guanghui; Tang, Tao; Wen, Jianfeng; Li, Xinyu
Abstract : Fluorinated graphene quantum dots (F-GQDs) were prepared by mixing GQDs and XeF2 in a facile gaseous phase heating method. The F-GQDs with excellent water solubility have a F/C atomic ratio of 84.25% and a diameter of 2–6 nm. The photoluminescence (PL) properties of GQDs and F-GQDs were investigated systematically. The results showed that the PL emission of the F-GQDs exhibited an obvious blue-shift of 90 nm compared to that of the GQDs.